An interactive learning approach to accounting classes - Carvalheiro, Jorge Fernando (2016)
This working paper explores the use of interactive learning tools, such as business simulations, to facilitate the active learning process in accounting classes. Although business simulations were firstly introduced in the United States in the 1950s, the vast majority of accounting professors still use traditional teaching methods, based in end-of-chapter exercises and written cases. Moreover, the current students’ generation brings new challenges to the classroom related with their video, game, internet and mobile culture. Thus, a survey and an experimentation were conducted to understand, on one hand, if accounting professors are willing to adjust their teaching methods with the adoption of interactive learning tools and, on the other hand, if the adoption of interactive learning tools in accounting classes yield better academic results and levels of satisfaction among students. Students using more interactive learning approaches scored significantly higher means than others that did not. Accounting professors are clearly willing to try, at least once, the use of an accounting simulator in classes.